Prescribing patterns of celecoxib and prescribers' perceptions among three general hospitals in Northern Malaysia - Huan-Keat Chan; Ema Bakri; Sing-Yi Tan; Mohamed Azmi Hassali; Fahad Saleem; Tahir Mehmood Khan (Archives of Global Professionals, 2014)
Objectives: This paper describes the clinical use of celecoxib in three major, government-subsidized hospitals across Northern Malaysia. Doctors' perceptions of issues related to celecoxib and other nonsteroidal anti-inflammatory drugs (NSAIDs) were assessed concurrently. Materials and Methods: A total of 365 patients receiving prescriptions containing celecoxib in 2012 were recruited. Their medical records were screened for celecoxib-related information including its indications, risk factors for gastrointestinal bleeding and cardiovascular comorbidities. A self-reported, six-item questionnaire was used to investigate the perceptions of 211 doctors. Results: Patients within a wide range of ages had received celecoxib (15-94 years). General acute pain (23.6%), general chronic pain (20.3%), and osteoarthritis (12.3%) were the most common indications. Less than one-third of patients prescribed with celecoxib (31.5%) were found to have one or more risk factors for gastrointestinal complications. Advanced age (≥65 years) was identified as the most common risk factor (14.8%). Approximately one-third of them (32.4%) were having one or more cardiovascular comorbidities including hypertension and chronic heart diseases. Majority of the doctors (53.1%) believed that celecoxib is more efficacious than conventional NSAIDs in reducing pain and inflammation. The awareness of its better gastrointestinal safety profile was exceptionally high (92.4%) and it remained as the most important factor to consider during prescribing (65.9%). Conclusion: Overall, this study revealed the prescribing patterns of celecoxib among the government-subsidized hospitals in Northern Malaysia. Certain issues like its high usage in patients without gastrointestinal risk factors and in those with cardiovascular comorbidities may require a review from clinical perspectives.